'El Capri Kylex': A Franciscan astronomical mnemonic. (August 2021) - Falk, Seb
This article examines the role of memory techniques in medieval astronomy. Using a mnemonic written by a Franciscan friar c. 1330 as a case study, it shows how astronomers and astrologers simplified the sky for practical purposes, using verses and codes to make their science memorable. The article decodes the mnemonic and its underlying astronomical data, assessing its usefulness, memorability and adaptability alongside some other popular astronomical and calendrical mnemonics of the later Middle Ages. It argues that astronomical learning could be a creative, playful activity. And it situates the astrological practices of this particular friar, who made wide-ranging annotations in a 13th-century astronomical compendium, within the scientific and educational traditions of his order.